- Survey-based Mapping of Households’ Vulnerability Towards A Comprehensive Evacuation Plan in Karang Kendal, Mt. Merapi - Depari, Catharina; Tjahyono, Suhodo (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2024)
To enhance resilience, a comprehensive evacuation map that considers the residents’ social vulnerability is critical. This paper aims to discuss this concern based on community service at Karang Kendal permanent housing in Mt. Merapi’s hazard zone level II, an area to which the Pelemsari community relocated and resided after the violent eruption in 2010. The planning methods used to create such a map are questionnaire surveys and field observations. The results indicate the highly vulnerable populations of the sub-village where 67% of the total 81 houses are occupied by 2-3 vulnerable residents and 68% of these populations are women. These findings then served as a basis for the making of an evacuation map that was not only integrated with the information on the distribution of vulnerable households but also capable of developing the residents’ awareness of disasters concerning their socio-demographic conditions.